Identifying the Underlying Mechanisms of Change During Acceptance and Commitment Therapy (Act): A Systematic Review of Contemporary Mediation Studies - Berrios-Espinoza, R (Cambridge University Press, 2019)
Background: Mediation studies test the mechanisms by which interventions produce clinical outcomes. Consistent positive mediation results have previously been evidenced (Hayes et al., 2006) for the putative processes that compromise the psychological flexibility model of acceptance and commitment therapy (ACT). Aims: The present review aimed to update and extend the ACT mediation evidence base by reviewing mediation studies published since the review of Hayes et al. (2006). Method: ACT mediation studies published between 2006 and 2015 were systematically collated, synthesized and quality assessed. Results: Twelve studies met inclusion criteria and findings were synthesized by (a) the putative processes under investigation, and (b) the outcomes on which processes were tested for mediation. Mediation results were found to be generally consistent with the psychological flexibility model of ACT. However, studies were limited in methodological quality and were overly focused on a small number of putative processes. Conclusions: Further research is required that addresses the identified methodological limitations and also examines currently under-researched putative processes. © 2018 British Association for Behavioural and Cognitive Psychotherapies.